Larcenists and Lambs - Pikora, Vladimír (TZ-one, 2017)
A thriller from the realms of high finance, based on events that are all-too-true…Immediately after publication in the Czech Republic, the book became a bestseller. In 2015 it won the Reader’s Award for Best Book in the prestigious Czech literary competition, the Magnesia Litera. What at first glance appears to be a run-of-the-mill madcap adventure story very quickly becomes a fundamental statement about the state of today’s financial world. What first appears to be a simple situation comedy unexpectedly turns into a sarcastic and visionary description of the world of finance and politics. The dry, situation-based humor gradually escalates into looming tension which culminates in an unexpected psychological revelation and a highly pertinent warning for all of society. The authors, leading Czech economists and authors of several bestsellers, have an insiders’ knowledge of the environment they describe. Each of the characters and events has a real role model in the real world, which the authors have altered to fit the needs of the plot. The most fantastic aspect of this book is that many of the warnings it gives, which seemed impossible when it was first published (for example the possible disintegration of the EU), have since come true! And many that still could, remain…In the book, an idiosyncratic couple is shocked to discover that under the surface of today’s society everything is different from what it seems at first glance. They find out more about how rotten the system is than even they themselves want to know –or than “others” want them to know. But who are these “others,” and why do they want to liquidate them? And can the approaching financial apocalypse and collapse of the entire financial system be averted?This book will change the way you see the people around you. And the notion that we all live in a Matrix will cease to seem impossible.